2013
DOI: 10.1155/2013/973179
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Nanoparticles Adsorbed to Polyethylene Glycol Microspheres as Activators of Human Colostrum Macrophages

Abstract: The effectiveness of hormones associated with polymeric matrices has amplified the possibility of obtaining new drugs to activate the immune system. Melatonin has been reported as an important immunomodulatory agent that can improve many cell activation processes. It is possible that the association of melatonin with polymers could influence its effects on cellular function. Thus, this study verified the adsorption of the hormone melatonin to polyethylene glycol (PEG) microspheres and analyzed its ability to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…The formation of the microspheres was thermally induced by subjecting the solution to 95°C for 5 min. For adsorption, the suspensions of PEG microspheres in PBS were incubated with melatonin (concentration 100 ng ml -1 ; Sigma) at 37°C for 30 min according to the method described by Hara et al [4]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the microspheres was thermally induced by subjecting the solution to 95°C for 5 min. For adsorption, the suspensions of PEG microspheres in PBS were incubated with melatonin (concentration 100 ng ml -1 ; Sigma) at 37°C for 30 min according to the method described by Hara et al [4]. …”
Section: Methodsmentioning
confidence: 99%
“…The adsorption capacity of the microspheres can be modified to improve the biological function of the organic compounds transported [3]. In an earlier study, we showed that PEG microspheres are a promising carrier for melatonin because they prevent the degradation of this hormone and increase its bioavailability, improving the immune response of the organism [4]. …”
Section: Introductionmentioning
confidence: 99%
“…It known that PEG nanoscale particle formulations can allow the control of the speed at which the drug is released from the polymer matrix [28]. In this sense the PEG nanoparticles have a high potential in the hormone transport system [19,20]. This material has biocompatible characteristics their degradation products do not present toxicity and are easily metabolized and excreted by natural physiological pathways [29].…”
Section: Discussionmentioning
confidence: 99%
“…PH = 6.8 using a modification of the described method [18,19,20]. For the synthesis of polyethylene glycol (PEG) nanoparticles (NP-PEG) with glycine adsorbed for the complex formation (NANO-PEG/GLY) PEG 6000 (10g) at the concentration of 0.016 mol/L, was diluted in 100 mL of phosphate buffered saline (PBS), incubated for 45 min at 45ºC.…”
Section: Synthesis and Preparation Of Peg Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation